1966
DOI: 10.2307/1935744
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure for Calculating Daily Moisture Stress and Its Utility in Regressions of Tree Growth on Weather

Abstract: A method is described for computing daily values of moisture stress on forest vegetation, or water deficits, based on the differences between Thornthwaite's potential evapo—transpiration and computed soil—moisture depletion. More realistic functions are used for soil—moisture depletion on specific soil types than have been customary. These functions related daily rates of depletion to characteristics of soil—moisture tension. Separate functions account for surface soil wetting and drying processes following ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In upland forests, the previous year's rainfall was also as important to tree-ring growth as current year rainfall (Tryon and True 1958;Zahner and Stage 1966). The needles of black spruce, for example, are formed in the bud the previous year and remain on the trees for several years.…”
Section: Discussionmentioning
confidence: 99%
“…In upland forests, the previous year's rainfall was also as important to tree-ring growth as current year rainfall (Tryon and True 1958;Zahner and Stage 1966). The needles of black spruce, for example, are formed in the bud the previous year and remain on the trees for several years.…”
Section: Discussionmentioning
confidence: 99%
“…They highlight the growth sensitivity of each species to monthly temperatures and precipitation. Additional physiological 0378 indices, such as related to soil water deficits (Zahner and Stage, 1966), are used rather than climatic data to allow biological interpretations of the growth response to climate. These indices could be better correlated with radial growth than monthly climatic variables (Foster and Leblanc, 1993) because soil water availability is a major limiting factor for tree growth.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have used daily climatic parameters to define "physiological" indices such as potential evapotranspiration, soil-moisture stress. (Zahner and Stage 1966;Zahner and Donnelly 1967;Giles et al 1985;Wickramasinghe 1988;Roberston et al 1990). In their physiological approach to dendroclimatic modeling of oak radial growth, Foster and LeBlanc (1993) clearly showed that individual physiological response indices were better correlated with radial growth than were monthly climatic variables, and were more amenable to biological interpretation than models using monthly climate variables.…”
Section: Introductionmentioning
confidence: 99%